MicroRNA-restricted transgene expression in the retina. - Marianthi Karali; Anna Manfredi; Agostina Puppo; Elena Marrocco; Annagiusi Gargiulo; Mariacarmela Allocca; Michele Della Corte; Settimio Rossi; Massimo Giunti; Maria Laura Bacci; Francesca Simonelli; Enrico Maria Surace; et al. (PLoS ONE)
Background Gene transfer using adeno-associated viral (AAV) vectors has been successfully applied in the retina for the treatment of inherited retinal dystrophies. Recently, microRNAs have been exploited to fine-tune transgene expression improving therapeutic outcomes. Here we evaluated the ability of retinal-expressed microRNAs to restrict AAV-mediated transgene expression to specific retinal cell types that represent the main targets of common inherited blinding conditions. Methodology/principal findings To this end, we generated AAV2/5 vectors expressing EGFP and containing four tandem copies of miR-124 or miR-204 complementary sequences in the 3'UTR of the transgene expression cassette. These vectors were administered subretinally to adult C57BL/6 mice and Large White pigs. Our results demonstrate that miR-124 and miR-204 target sequences can efficiently restrict AAV2/5-mediated transgene expression to retinal pigment epithelium and photoreceptors, respectively, in mice and pigs. Interestingly, transgene restriction was observed at low vector doses relevant to therapy. Conclusions We conclude that microRNA-mediated regulation of transgene expression can be applied in the retina to either restrict to a specific cell type the robust expression obtained using ubiquitous promoters or to provide an additional layer of gene expression regulation when using cell-specific promoters.